1996
DOI: 10.1103/physreve.53.4107
|View full text |Cite
|
Sign up to set email alerts
|

Analytic expressions for the electromagnetic mode density in finite, one-dimensional, photonic band-gap structures

Abstract: We derive an exact expression for the electromagnetic mode density, and hence the group velocity, for a finite, N-period, one-dimensional, photonic band-gap structure. We begin by deriving a general formula for the mode density in terms of the complex transmission coefficient of an arbitrary index profile. Then we develop a specific formula that gives the N-period mode density in terms of the complex transmission coefficient of the unit cell. The special cases of mode-density enhancement and suppression at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
380
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(403 citation statements)
references
References 31 publications
14
380
1
1
Order By: Relevance
“…We have found that here , where is a fitting constant. This result is similar to that of Dowling [20], who analytically calculated the DOS as function of sample thickness in a dielectric medium with alternating refractive indices. We then write for the pump energy at lasing threshold:…”
Section: Threshold Dependence On Cell Thicknesssupporting
confidence: 88%
“…We have found that here , where is a fitting constant. This result is similar to that of Dowling [20], who analytically calculated the DOS as function of sample thickness in a dielectric medium with alternating refractive indices. We then write for the pump energy at lasing threshold:…”
Section: Threshold Dependence On Cell Thicknesssupporting
confidence: 88%
“…15,18 The limits imposed on the minimum attainable group velocity in photonic crystals have been studied in various contexts, such as, e.g., fabrication disorder, 19,20 lossy dielectrics, 21 and finitesize effects. 22 It is the aim of this Brief Report to generalize these findings and to show that they may all be presented in the context of broadening of electromagnetic modes and the resulting induced density of states ͑DOS͒.…”
Section: Limits Of Slow Light In Photonic Crystalsmentioning
confidence: 89%
“…In general, the study of electromagnetic properties of such materials is very complicated, and the dispersion relation we need to evaluate the phase time in the proposed formalism is quite involved for physical situations. This study was performed analytically in [15] where the dispersion relation (and other useful quantities) was derived starting from the complex transmission coefficient of the considered barrier. It is, then, quite a meaningless issue to get the tunnelling time from the dispersion relation obtained from the transmission coefficient, while it is easier to have directly the phase time τ from Eq.…”
Section: Photonic Bandgapmentioning
confidence: 99%
“…We again assume normal incidence of the light on the photonic bandgap material. In this case the transmission coefficient T and its phase φ have the expressions as in (34) and (45), where A,B are given by (35), (36) and [15]:…”
Section: B Distributed Bragg Reflectormentioning
confidence: 99%